B14. Novel Treatments for Lung Infections: Modulating Immune Responses 2011
DOI: 10.1164/ajrccm-conference.2011.183.1_meetingabstracts.a2498
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 And M2A Alveolar Macrophages Promote Lung Defense Against The Atypical Fungal Pathogen Pneumocystis Murina

Abstract: We have recently reported that mice deficient in the myeloid Src-family tyrosine kinases Hck, Fgr, and Lyn (Src triple knockout [TKO]) had augmented innate lung clearance of Pneumocystis murina that correlated with a higher ability of alveolar macrophages (AMs) from these mice to kill P. murina. In this article, we show that despite possessing enhanced killing, AMs from naive Src TKO mice did not demonstrate enhanced inflammatory responses to P. murina. We subsequently discovered that both AMs and lungs from P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 23 publications
2
34
0
1
Order By: Relevance
“…Results in Fig. 3A show that Src TKO mice had increased Mmp12 expression in the lungs 7 days after P. murina lung challenge, a time point at which M2 signature genes are increased (28). It is important to note that Src TKO mice had enhanced Mmp12 expression by day 7, which is a week earlier than wild-type control mice express significant Mmp12 in the lungs (Fig.…”
Section: P Murina Lung Exposure Results In the Induction Of Mmp12mentioning
confidence: 87%
See 2 more Smart Citations
“…Results in Fig. 3A show that Src TKO mice had increased Mmp12 expression in the lungs 7 days after P. murina lung challenge, a time point at which M2 signature genes are increased (28). It is important to note that Src TKO mice had enhanced Mmp12 expression by day 7, which is a week earlier than wild-type control mice express significant Mmp12 in the lungs (Fig.…”
Section: P Murina Lung Exposure Results In the Induction Of Mmp12mentioning
confidence: 87%
“…We have recently reported that macrophage activation during P. murina lung infection in resistant mice favors alternative macrophage activation (28). Although MMP12 expression may be associated with alternative macrophage activation (14), data also support a role for IFN-␥ in the induction of MMP12 (10,19).…”
Section: P Murina Lung Exposure Results In the Induction Of Mmp12mentioning
confidence: 88%
See 1 more Smart Citation
“…In Pneumocystis murina lung infection, IL-33 enhances the killing activity of macrophages (33). An IL-33-mediated reduction of Pseudomonas aeruginosa-induced corneal keratitis correlates with M2 macrophage polarization and the decrease in bacterial numbers in the cornea (34).…”
Section: Discussionmentioning
confidence: 99%
“…IL-33 acts on a variety of cells of the innate arm of immunity, including neutrophils, macrophages, dendritic cells, mast cells, basophils, and eosinophils, and functions as an amplifier of inflammation (5)(6)(7)(8)(9)(10)(11)(12)(13). Recent studies have suggested that IL-33 plays a role in infection-related inflammation, as IL-33 is protective against infection by opportunistic pathogens such as Pseudomonas aeruginosa, Pneumocystis murina, Cryptococcus neoformans, and polymicrobes (6,8,9,14). Prior to this study, there had been no publications regarding the role of IL-33 in Candida albicans infections.…”
mentioning
confidence: 99%